Analysis of the efficiency of financial and economic activities of russian football clubs - A. A. Aliev; O. V. Litvishko; A. I. Yusifova; A. A. Fateeva (Вестник университета, 2021)
Attracting financing and a stable inflow of capital investments for development is one of the most important issues in the framework of a market economy for any sphere, including the professional sports industry. The inflow of sufficient funding depends to a high degree on the investment attractiveness of the object. In addressing these issues, an essential role is played by the assessment of the effectiveness of financial and economic activities, which affects the amount of funds raised from both budgetary and extra-budgetary sources. The identification of the most important performance factors will allow us to direct efforts to maintain their favorable condition, which is the key to the stable development of the sports industry. The conducted analysis showed that with a competent approach, in particular in the issues of popularization of the sport, the league and club brand, customer orientation and the use of the product exclusivity factor, qualified personnel, as well as investment and innovation activity, including in the issue of training sports personnel, the professional sports industry can be considered as an effective investment and advertising tool that can generate income both in monetary form and in the form of image and socially significant effect.